Characterization of histamine receptors in tracheal smooth muscle of Mastomys natalensis - Shukla Rakesh; Srimal Rikhab Chand; Dhawan Bhola Nath (Acta Pharmacologica Sinica, 2016)
The tracheal smooth muscle of Mastomys natalensis contracted with carbachol administration while histamine (H) caused concentration-dependent relaxation. The Specific H2-receptor agonists 4-methyl histamine, dimaprit, impromidine and a high concentration of 2-methyl histamine (H1-agonist) caused relaxation similar to H which was selectively blocked by cimetidine. Low concentrations (10(-5)-10(-4) mol/L) of 2-methyl histamine and of H (10(-8)-10(-7) mol/L) occasionally produced small contractions. Mepyramine (pyrilamine) blocked the contraction but did not modify the relaxant effect of H and its agonists. The results suggest a preponderance of histamine H2-inhibitory receptors in the trachea of this animal.